Outsourcing-The New Paradigm - Vijay Kumar, R.; Chelvan, G.Thamizh (Indian Journal of Marketing, 2004)
The faster growth of communication and the Internet facilities have made the whole world as one market. The business enterprises are modifying and changing their strategic positions due to the increased pressure of the globalization, cut throat competition existing in the market and the general depression in the economy of the countries. With a view to ensure the profitability in the operations of the enterprises and to regain the competitive advantages, they have to find out new and efficient ways of utilizing their energies both in terms of resources and core competence. With a view to minimize cost and achieve efficiency, the companies are outsourcing their functions. In order to gain cost advantage and competitive advantage, the companies determine the whole activities as core and non-core activities and also find out the activities, where outsourcing is possible.